Immunotherapy following hematopoietic stem cell transplantation: potential for synergistic effects. (May 2010) - Bouchlaka, Myriam N; Redelman, Doug; Murphy, William J
Hematopoietic stem cell transplantation (HSCT) is a particularly important treatment for hematologic malignancies. Unfortunately, following allogeneic HSCT, graft-versus-host disease, immunosuppression and susceptibility to opportunistic infections remain among the most substantial problems restricting the efficacy and use of this procedure, particularly for cancer. Adoptive immunotherapy and/or manipulation of the graft offer ways to attack residual cancer as well as other transplant-related complications. Recent exciting discoveries have demonstrated that HSCT could be expanded to solid tissue cancers with profound effects on the effectiveness of adoptive immunotherapy. This review will provide a background regarding HSCT, discuss the complications that make it such a complex treatment procedure following up with current immunotherapeutic strategies and discuss emerging approaches in applying immunotherapy in HSCT for cancer.